Disease-Modifying, Neuroprotective Effect of N-Acetyl-l-Leucine in Adult and Pediatric Patients With Niemann-Pick Disease Type C - Patterson, Marc C; Ramaswami, Uma; Donald, Aimee; Foltan, Tomas; Gautschi, Matthias; Gissen, Paul; Hahn, Andreas; Jones, Simon A; Kay, Richard; Kolniková, Miriam; Park, Julien; Reichmannová, Stella; et al. (Neurology, 2025)
BACKGROUND AND OBJECTIVES: N-acetyl-l-leucine (NALL) has been established to improve the neurologic manifestations of Niemann-Pick disease type C (NPC) after 12 weeks in a placebo-controlled trial. In the open-label extension phase (EP) follow-up, data were obtained after 12 and 18 months to evaluate the long-term effects of NALL for NPC. METHODS: This is an ongoing, multinational, multicenter EP. Patients with a genetic diagnosis of NPC aged 4 years or older who completed the placebo-controlled trial were eligible to continue in the EP and receive orally administered NALL 2-3 times per day in 3 tiers of weight-based dosing. The primary end point is the modified 5-domain NPC Clinical Severity Scale (NPC-CSS) (range 0-25 points; lower score representing better neurologic status); data from the EP cohort are compared with the expected annual trajectory of decline (i.e., disease progression) established in natural history studies. Analyses are also performed on exploratory end points, including the 15-domain and 4-domain NPC-CSSs and the Scale for Assessment and Rating of Ataxia (SARA). RESULTS: Fifty-three patients aged 5-67 years (45.3% female, 54.7% male) were enrolled in the EP. After 12 months, the mean (±SD) change from baseline on the 5-domain NPC-CSS was -0.27 (±2.42) with NALL vs +1.5 (±3.16) in the historical cohort (95% CI -3.05 to -0.48; p = 0.009), corresponding to a 118% reduction in annual disease progression. After 18 months, the mean (±SD) change was +0.05 (±2.95) with NALL vs +2.25 (±4.74) in the historical cohort (95% CI -4.06 to -0.35; p = 0.023). The 15-domain and 4-domain NPC-CSSs were consistent with the 5-domain NPC-CSS. The improvements in neurologic manifestations demonstrated in the placebo-controlled trial on the primary SARA end point were sustained over the long-term follow-up. NALL was well tolerated, and no treatment-related adverse events or serious reactions occurred. DISCUSSION: Treatment with NALL was associated with a significant reduction in NPC disease progression after 12 and 18 months, demonstrating a disease-modifying, neuroprotective effect. TRIAL REGISTRATION INFORMATION: The trial is registered with ClinicalTrials.gov (NCT05163288; registered December 6, 2021), EudraCT (2021-005356-10). The first patient was enrolled into the EP on March 8, 2023. The trial was funded by IntraBio Inc. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that NALL reduces disease progression in NPC.
Keywords: výsledek terapie; Young Adult; Male; neuroprotektivní látky; Child, Preschool; leucin; progrese nemoci; mladý dospělý; následné studie; Adolescent; Niemannova-Pickova nemoc typu C; Child; dítě; Adult; dospělí; Leucine; mužské pohlaví; Niemann-Pick Disease, Type C; Neuroprotective Agents; Disease Progression; Severity of Illness Index; mladiství; Follow-Up Studies; dvojitá slepá metoda; Treatment Outcome; předškolní dítě; lidé; ženské pohlaví; Humans; stupeň závažnosti nemoci; Double-Blind Method; Female; lidé středního věku; Middle Aged